Preparation of hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fireproof coating

By loading the nanocomposite flame retardant of Hexachlorocyclotriphosphazene coated with Co/Zn-MOF microcapsules on the surface of boron nitride, combined with aqueous epoxy resin, a high-performance epoxy expansion fire-retardant coating was prepared, which solved the steel structure The problem of fire risk has significantly improved fire resistance and heat insulation.

CN119242134AActive Publication Date: 2025-01-03CHENGDU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411514411.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-03
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The high thermal conductivity of steel structures leads to high fire risk. The existing water-based epoxy resin fire-retardant coatings are flammable and difficult to effectively retardant. It is necessary to develop high-performance multifunctional composite nanofire retardant to improve fire resistance.

Method used

Hexachlorocyclic triphosphazene is coated in Co/Zn-MOF microcapsules and loaded on the surface of boron nitride to form a multifunctional and efficient nanocomposite flame retardant, and combined with it to prepare high-performance epoxy in aqueous epoxy resin Expansion fire-retardant coating.

Benefits of technology

Through the porous structure of Co/Zn-MOF and the gas-phase flame retardant effect of HCCP, the flame retardant performance of the polymer is significantly improved, the flame retardant effect and residual carbon amount of the carbon layer are increased, and the temperature of the steel structure in fire is significantly reduced. The rise speed improves the thermal insulation and thermal insulation performance of fire-resistant coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005106310480000061
    Figure BDA0005106310480000061
  • Figure BDA0005106310480000101
    Figure BDA0005106310480000101
  • Figure HDA0005106310520000011
    Figure HDA0005106310520000011
Patent Text Reader

Abstract

The invention discloses a hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fireproof coating. A preparation method of the coating comprises the following steps: (1) preparing a BN (at) PDA-MOF (at) HCCP (BM (at) PH) flame retardant; (2) preparing a BM-coated PH epoxy expansion fireproof coating; the multifunctional efficient boron nitride-based epoxy expansion fireproof coating is prepared by combining the excellent barrier property of BN, the synergistic catalytic char formation flame retardant effect of bimetal ions in Co / Zn-MOF and the gas-phase flame retardant effect of a high-phosphorus-nitrogen HCCP flame retardant. During combustion of a coating sample, a sample of BM at PH exhibits a lowest back temperature (163.2 DEG C), a maximum expansion height (31 mm) and an expansion rate (24.2%), indicating the most excellent thermal insulation properties thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of epoxy water-based intumescent fire-retardant coatings, and specifically relates to the preparation of a hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fire-retardant coating. Background Art

[0002] Nowadays, steel structures are widely used in buildings, bridges and tunnels due to their remarkable ductility and mechanical properties; however, the high thermal conductivity of steel structures leads to a high fire risk, so fire protection of steel structures is crucial to the safety of their application; among many fire protection technologies, intumescent fire retardant coatings are popular due to their excellent performance and low price; generally speaking, intumescent fire retardant coatings are mainly composed of polymers, expanding components and fillers. In terms of polymer composition, water-based epoxy resins have attracted widespread attention due to their excellent adhesion and environmental protection; however, similar to most polymer materials, water-based epoxy resins are inherently flammable and prone to fire; therefore, research on the flame retardancy of water-based epoxy resins has important practical significance; a large number of studies have shown that the addition of inorganic nano-flame retardants can effectively improve their fire resistance; therefore, developing a multifunctional composite nano-flame retardant with excellent performance has become an effective way to solve this problem. Summary of the invention

[0003] Hexagonal boron nitride (BN) is an emerging two-dimensional layered material, mainly composed of B and N atoms, and has a two-dimensional layered structure similar to graphene; more importantly, it has excellent high temperature resistance, thermal stability, antioxidant and high barrier properties, which can effectively block oxygen entry, volatiles overflow, and inhibit heat / flame transfer, so it is considered to be a very promising inorganic nano flame retardant material; Metal-organic framework materials (MOFs) are a class of highly regular porous crystalline nanomaterials formed by the coordination of metal ions or metal oxides with organic linkers. It has a unique pore structure and extremely high specific surface area. This porosity helps to adsorb and store small molecules, making it have great application potential in adsorption and encapsulation technology; in addition, during the combustion process, the metal ions in MOFs can promote the formation of residual carbon in the combustion process, increase the amount of residual carbon, and thus improve the flame retardant effect of the carbon layer; therefore, MOFs is a promising capsule material and metal catalytic flame retardant precursor; hexachlorocyclotriphosphazene (HCCP) is a phosphorus-containing inorganic compound with the advantages of being environmentally friendly and non-toxic. Its molecule contains a large amount of phosphorus (about 26.73%). During the combustion process, the phosphorus free radicals generated by the decomposition of HCCP can effectively capture H- and OH-free radicals, thereby interrupting the combustion reaction. HCCP is a very excellent phosphorus-containing biological flame retardant; the present invention adopts a simple one-step method to encapsulate hexachlorocyclotriphosphazene (HCCP) in the pores of Co / Zn-MOFs, and then loads the hexachlorocyclotriphosphazene bimetallic MOF microcapsule on the surface of boron nitride, thereby obtaining a new multifunctional and efficient nano-composite flame retardant; then the new multifunctional and efficient nano-composite flame retardant is added to a water-based epoxy resin matrix to successfully prepare a high-performance and multifunctional epoxy intumescent fire retardant coating.

[0004] To achieve the above purpose, the technical solution adopted by the present invention to solve its technical problem is.

[0005] The invention discloses a preparation method of a hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fireproof coating, comprising the following steps.

[0006] 1. Preparation of BN@PDA-MOF@HCCP (BM@PH) flame retardant.

[0007] (1) First, boron nitride (BN) was ultrasonically dispersed in 100 mL of deionized water to obtain a uniformly dispersed boron nitride suspension. Then, tris-HCl was added to the boron nitride suspension and stirred evenly, followed by the addition of dopamine hydrochloride. The pH of the boron nitride mixed solution was adjusted to 8.5 and then stirred at room temperature for 24 h. Finally, the mixture was repeatedly washed with deionized water to remove excess reactants, and the boron nitride / polydopamine (BN@PDA) hybrid was obtained by high-speed centrifugation.

[0008] (2) BN@PDA was ultrasonically dispersed in 100 mL of methanol solution, and Zn(NO3)2:6H2O and Co(NO3)2:6H2O powders were added and stirred for 10-20 min. HCCP was then added to the BN@PDA dispersion and stirred for 5-10 min. Then, dimethylimidazole (2-MIM) was added to the BN@PDA dispersion. After stirring for 30 min, the BN@PDA dispersion was transferred to a hydrothermal autoclave and reacted at 140 °C for 16-20 h. Finally, the precipitate was repeatedly washed by centrifugation with methanol to obtain the BN@PDA-MOF@HCCP (BM@PH) flame retardant.

[0009] 2. Preparation of BM@PH epoxy intumescent fire retardant coating.

[0010] Firstly, melamine (MEL), pentaerythritol (PER) and ammonium polyphosphate (APP) are dispersed in deionized water and stirred vigorously until a uniform expansion system mixture is obtained; then, BM@PH flame retardant is ultrasonically dispersed in deionized water to obtain BM@PH flame retardant suspension, and the BM@PH flame retardant suspension, water-based epoxy resin emulsion and curing agent are mixed and stirred for 10-20 minutes and then poured into the expansion system mixture at one time to obtain a uniformly dispersed BM@PH-based water-based epoxy slurry; finally, the BM@PH-based water-based epoxy slurry is evenly coated on a steel plate with a sandblasting grade of Sa2, and after brushing, it is cured at room temperature for 7 days to obtain a BM@PH epoxy expansion fire retardant coating.

[0011] Furthermore, in step 1(1), the mass ratio of dopamine hydrochloride to boron nitride is 1:1-2.

[0012] Furthermore, in step 1(1), the mass ratio of tris-HCl to dopamine hydrochloride is 1:1-1.5.

[0013] Furthermore, in step 1(2), the mass ratio of Zn(NO3)2:6H2O to BN@PDA is 1:1-2.

[0014] Furthermore, in step 1(2), the molar ratio of Zn(NO3)2:6H2O to Co(NO3)2:6H2O is 3-1:1.

[0015] Furthermore, in step 1(2), the molar ratio of Zn(NO3)2:6H2O and 2-MIM is 1:4-8.

[0016] Furthermore, in step 1(2), the mass ratio of Zn(NO3)2:6H2O and HCCP is 1:0.4-1.

[0017] Furthermore, in step 2, the mass ratio of polyphosphate, dipentaerythritol and melamine is 5-7:2-4:0.5-1.5.

[0018] Furthermore, in step 2, the mass ratio of epoxy resin, curing agent and expansion system is 2-2.5:1:0.8-1.2.

[0019] Furthermore, in step 2, the curing agent is ethylenediamine, diethylenetriamine, or triethylenetetramine.

[0020] Furthermore, in step 2, the total weight of the waterborne epoxy resin emulsion, curing agent, melamine, pentaerythritol and ammonium polyphosphate accounts for 95.0-97.0% of the total weight of the uniformly dispersed system.

[0021] Furthermore, in step 2, the BM@PH flame retardant accounts for 3.0-5.0% of the total weight of the uniformly dispersed system.

[0022] The hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fire-retardant coating provided by the present invention combines the excellent barrier properties of BN, the flame-retardant effect of the synergistic catalytic carbonization of bimetallic ions in Co / Zn-MOF and the gas-phase flame-retardant effect of high-phosphorus-nitrogen HCCP flame retardant to prepare a multifunctional and efficient boron nitride-based epoxy intumescent fire-retardant coating; the successful development of this product can promote the application of multifunctional nano-composite flame retardants in fire-retardant coatings, and has important application research value for the large-scale production of fire-retardant coatings.

[0023] In addition, the preparation of a hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fire-retardant coating provided by the present invention has the following beneficial effects.

[0024] (1) The Co / Zn-MOF microcapsules encapsulated with HCCP can be uniformly loaded on the surface of boron nitride. The porous structure and large surface area of ​​Co / Zn-MOF increase the catalytic active sites, effectively improving the ability of the flame retardant to catalyze the carbonization of the resin matrix, thereby achieving the purpose of improving the flame retardant properties of the polymer.

[0025] (2) Co / Zn-MOF as a microcapsule shell not only has the beneficial advantages of controllable structure and adjustable pore size, but also can pyrolyze at high temperature to produce metal oxides, play the role of metal catalysis to carbonize, and greatly improve the quality of the residual carbon layer.

[0026] (3) The phosphorus radicals generated by the decomposition of HCCP stored in Co / Zn-MOFs at high temperature can effectively capture the H· and OH· radicals generated during the combustion of the polymer, thus playing a role in gas-phase flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1SEM images of (a) BN, (b) BN@PDA, (c) Co / Zn-MOF, (d) Co / Zn-MOF@HCCP and (ef) BM@PH and EDS spectra of (gl) BM@PH.

[0028] Figure 2 XRD patterns of BN, BN@PDA, Co / Zn-MOF, Co / Zn-MOF@HCCP, and BM@PH hybrids.

[0029] Figure 3 FTIR spectra of BN, BN@PDA, Co / Zn-MOF, Co / Zn-MOF@HCCP, and BM@PH hybrids.

[0030] Figure 4 TGA and DTG spectra of BN, BN@PDA, Co / Zn-MOF, Co / Zn-MOF@HCCP, and BM@PH hybrids.

[0031] Figure 5 Digital photos of pure (a, g) EP, (b, h) BN / EP, (c, i) BN@PDA / EP, (d, j) Co / Zn-MOF / EP, (e, k) Co / Zn-MOF@HCCP / EP and (f, l) BM@PH / EP plates before and after combustion.

[0032] Figure 6 This is a curve diagram of the temperature change on the back of the steel sheet and samples with different coatings.

[0033] Figure 7 Macroscopic photographs of (a) pure EP, (b) BN / EP, (c) BN@PDA / EP, (d) Co / Zn-MOF / EP, (e) Co / Zn-MOF@HCCP / EP and (f) BM@PH / EP after expansion test.

[0034] Figure 8 The expansion height and expansion rate diagram of different samples. DETAILED DESCRIPTION

[0035] Example 1.

[0036] The invention discloses a preparation method of a hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fireproof coating, comprising the following steps.

[0037] 1. Preparation of BN@PDA-MOF@HCCP (BM@PH) flame retardant.

[0038] (1) First, 0.5 g of boron nitride (BN) was ultrasonically dispersed in 100 mL of deionized water to obtain a uniformly dispersed boron nitride suspension. Then, 0.2 g of tris-HCl was added to the boron nitride suspension and stirred evenly, followed by 0.35 g of dopamine hydrochloride. The pH of the boron nitride mixed solution was adjusted to 8.5 and continued to be stirred at room temperature for 24 h. Finally, the mixture was repeatedly washed with deionized water to remove excess reactants, and the boron nitride / polydopamine (BN@PDA) hybrid was obtained by high-speed centrifugation.

[0039] (2) 0.5 BN@PDA was ultrasonically dispersed in 100 mL of methanol solution, and 0.5 g Zn(NO3)2:6H2O and 0.5 g Co(NO3)2:6H2O powder were added and stirred for 10-20 min. Then, 0.25 g HCCP was added to the BN@PDA dispersion and the mixture was stirred for 5-10 min. Then, 0.95 g dimethylimidazole (2-MIM) was added to the BN@PDA dispersion. After stirring for 30 min, the BN@PDA dispersion was transferred to a hydrothermal reactor and reacted at 140 °C for 16-20 h. Finally, the precipitate was washed by repeated centrifugation with methanol to obtain the BN@PDA-MOF@HCCP (BM@PH) flame retardant.

[0040] 2. Preparation of BM@PH epoxy intumescent fire retardant coating.

[0041] First, 10 g of melamine (MEL), 10 g of pentaerythritol (PER) and 20 g of ammonium polyphosphate (APP) were dispersed in deionized water and stirred vigorously until a uniform expansion system mixture was obtained; then, 4 g of BM@PH flame retardant was ultrasonically dispersed in deionized water to obtain a BM@PH flame retardant suspension, and the BM@PH flame retardant suspension, 38 g of water-based epoxy resin emulsion and 19 g of curing agent were mixed and stirred for 10-20 minutes and then poured into the expansion system mixture at one time to obtain a uniformly dispersed BM@PH-based water-based epoxy slurry; finally, the BM@PH-based water-based epoxy slurry was evenly coated on a steel plate with a sandblasting grade of Sa2, and after brushing, it was cured at room temperature for 7 days to obtain a BM@PH epoxy expansion fire retardant coating; the compositions of different water-based expansion fire retardant coatings are shown in Table 1.

[0042] Table 1 Composition of different water-based intumescent fire retardant coatings

[0043]

[0044] Experimental example 1.

[0045] This experimental example shows the experimental analysis results of a hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fire retardant coating.

[0046] BN, BN@PDA, Co / Zn-MOF, Co / Zn-MOF@HCCP, BM@PH composite flame retardants and expansion system suspensions were added to the water-based epoxy resin and curing agent mixed system to prepare 4wt.% coatings respectively; then, the evenly dispersed coating system was brushed on the surface of the pretreated steel sheet and cured at room temperature for 7 days to obtain the sample coating; in addition, the experiment used pure EP coating as a control.

[0047] (1) The microstructures of BN, BN@PDA, Co / Zn-MOF, Co / Zn-MOF@HCCP, and BM@PH flame retardants were observed by SEM. Figure 1 shown; from Figure 1 (a) It can be seen that pure BN does not show a specific morphology and exists mainly in an aggregated state; Figure 1 As shown in (b), dopamine (DA)-modified BN@PDA shows a similar structure, but is relatively dispersed compared to BN, indicating that dopamine modification can change the dispersion state of BN; for Co / Zn-MOF hybrid ( Figure 1 (c)), it can be clearly observed that the particles are in the state of regular octahedrons, and the particle size is as large as 50-100 nanometers. Figure 1 (d) It can be seen that the HCCP-coated Co / Zn-MOF particles still exist in the form of regular octahedrons, but the particle size is 5-10 times larger than that of Co / Zn-MOFs and the surface is relatively rough, which indicates that HCCP is coated in the pores of Co / Zn-MOFs, increasing the volume of Co / Zn-MOFs and thus changing its microscopic morphology; Figure 1 As shown in (e), the HCCP-coated Co / Zn-MOFs are anchored on the BN@PDA surface, and the small particles are evenly distributed. This is due to the modification of dopamine, which improves the binding force and dispersion between MOFs and BN. In addition, the element distribution map of the BM@PH hybrid surface ( Figure 1 (fl)) shows that Zn, Co, P, N, B, and Cl elements are uniformly distributed throughout the BN, indicating that Zn, Co, and P ions are uniformly doped into the BN structure, which is crucial to fully exert the synergistic effect among them.

[0048] (2) The XRD diffraction curves of BN, BN@PDA, MOF, HCCP, Co / Zn-MOF@HCCP and BM@PH nanohybrids are shown in Figure 2As shown; it can be clearly seen from BN and BN@PDA that a series of peaks at 26.7°, 41.6°, 43.7°, 50.1° and 55.2° are consistent with the (002), (100), (101), (004) and (110) crystal planes; the spectrum shows that Co / Zn-MOF@HCCP particles have high crystallinity and sharp diffraction peaks. The diffraction peaks of Co / Zn-MOF are at 2θ=10.3°, 12.7°, 14.6°, 16.4°, 18.0° The main peaks at 19.4°, 22.1°, 24.4°, 25.5° and 26.7° are consistent with those of Co / Zn-MOF@HCCP, and the main peak of HCCP can be found in the spectrum of Co / Zn-MOF@HCCP, indicating the existence of HCCP in Co / Zn-MOF; the characteristic diffraction behaviors of BN@PDA and MOF@HCCP can be simultaneously monitored in the diffraction spectrum of BM@PH nanohybrid, further confirming the successful preparation of BM@PH nanohybrid.

[0049] (3) The chemical composition of the material was tested by infrared spectroscopy (FT-IR). The results are as follows: Figure 3 As shown, the BN nanosheets have a peak at 1373 cm -1 With 815cm -1 The characteristic peaks at 2921cm-1 are attributed to the stretching vibration of the in-plane ring and the bending vibration of the out-plane ring of the BN bond. However, in BN@PDA, the functional groups of the PDA layer polymerized on the BN surface cannot be clearly observed, which is due to its lower signal intensity and the masking by the -OH, -NH and -BN bonds in the BN nanosheets. However, compared with pure N, the peak at 2921cm-1 is -1 The stretching vibration peak of the alkyl group appeared at 1633 cm -1 With 1060cm -1 The stretching vibration peak of the benzene ring and the characteristic peak of the CO bond in PDA appeared at 3121 cm -1 , 2926cm -1 , 1581cm -1 , 1142cm -1 , and 991cm -1 The peak at 422cm belongs to the stretching vibration peak of CH and CN bonds, while the peak at 422cm -1 and 990cm -1 The peaks at 964 belong to the stretching vibration peaks of Zn-N bond and Co-N bond respectively; the above data results confirm the successful synthesis of Co / Zn-MOF crystal; in the spectrum of HCCP, it can be seen that -1 and 1178cm -1The PN and P=O stretching vibration peaks at reflect the phosphorus-containing groups in HCCP, and these peaks indicate the structural characteristics of HCCP; in the spectrum of Co / Zn-MOF@HCCP, the characteristic peaks of Co / Zn-MOF and HCCP are observed to exist simultaneously, indicating that HCCP has been successfully coated on the surface of MOF, but at the same time, no significant chemical bonding occurs between the two; this physical bonding indicates that HCCP on the surface of Co / Zn-MOF is mainly attached through weak interactions; in the spectrum of BM@PH composite material, it can be seen that the characteristic peaks of BN, Co / Zn-MOF and HCCP still exist; there may be hydrogen bonds or electrostatic interactions between the hydroxyl and amino functional groups of the PDA modified layer and Co / Zn-MOF and HCCP, so a more complex peak shape appears in the spectrum of BM@PH, which strongly reflects the successful formation of the composite hybrid.

[0050] (4) When exposed to high heat, the thermal mass loss state of the composite coating is as follows Figure 4 The thermogravimetric data are shown in Table 2; all samples show two main decomposition processes in the range of 25-800 °C, namely the evaporation of adsorbed water in the range of 50-180 °C and the high-temperature pyrolysis of the polymer matrix between 200-550 °C; in addition, it can be clearly seen from the figure that the pyrolysis temperature increases after the addition of BN and BN@PDA, which may reflect the effect of BN nanosheet spacers; however, the maximum decomposition temperature of EP filled with Co / Zn-MOF and Co / Zn-MOF@HCCP decreases, which is due to the addition of Co 2+ 、Zn 2+ The synergistic catalytic effect of BN@PDA and MOF@HCCP nanosheets promotes the early decomposition of the polymer; the pyrolysis temperature of BM@PH is intermediate, which is the result of the synergistic effect of BN@PDA and MOF@HCCP nanosheets; the carbon residues of pure intumescent coatings, BN / EP, BN@PDA / EP, MOF / EP, MOF@HCCP / EP and BM@PH / EP are 17.8%, 18.4%, 19.2%, 20.3%, 21.9% and 24.2%, respectively; the increase in carbon residues of BN / EP and BN@PDA / EP composite intumescent coatings is mainly due to the barrier effect of BN nanosheets, while the higher carbon residue in BN / PDA-based EP is due to the formation of a stable CN network structure and improved dispersion after PDA decomposition; the higher carbon residue retained by MOF-enhanced EP swelling coating is partly attributed to the fact that MOF@HCCP nanosheets hinder the loss of cracked materials to the air to a certain extent, while Co 2+ 、Zn 2+and phosphate catalyzes more ring formation and the coking of cracking small molecules, which are retained in the coke; the BM@PH-supported EP swelling coating shows the highest coke retention after experiencing a high temperature of 800 °C, which is the result of the combination of the significant blocking ability of BN and the effective promotion of coke formation by MOF@HCCP.

[0051] Table 2 Thermogravimetric data of different samples

[0052]

[0053] (5) The surface condition of the composite coating before and after the large plate combustion test is as follows Figure 5 as shown; Figure 5 As shown in (af), it can be clearly observed that all samples showed a smooth and flat surface without any defects before combustion; after the large plate combustion test, the surfaces of different samples showed different states; the middle part of the carbon layer of pure EP ( Figure 5 (g)) was almost completely peeled off after combustion, exposing the steel substrate, which laid the foundation for its poor thermal insulation effect; the carbon layer of the BNI / EP composite coating ( Figure 5 (h)) does not show a large degree of peeling, but a small part of the carbon layer still falls off, which helps the penetration of heat and flames; for the EP composite coating filled with BN@PDA (Figure 5(i)), the carbon layer is more completely retained, which helps to block the external heat intrusion path, but holes still appear; for the EP composite coating with MOF added ( Figure 5 (j)), there are still holes on the surface of the coke layer, which may be due to the lack of boron nitride, which reduces the barrier effect on external flames; after adding MOF@HCCP ( Figure 5 (k)), fine cracks still appear on the surface of the layer; when BM@PH hybrid is added to EP ( Figure 5 (l)), the carbon layer on the substrate surface shows no obvious defects, such as macropores, cracks, etc., which determines the most excellent barrier effect against external high temperature.

[0054] (6) The backside temperature of the steel plate is directly related to the thermal insulation performance of the coating. The changes in the backside temperature of different samples during the combustion process are shown in Figure 2. Figure 6As shown; it can be seen that the back temperature of the uncoated steel plate rises rapidly to nearly 500°C in a short time, which will cause serious damage to its own strength; for the steel plate with pure EP coating, the rising rate of the back temperature is significantly reduced and finally stabilized at 230.8°C, which proves its effective protective effect; after adding BN, the back temperature of the steel plate drops to 199.4°C, indicating that BN can improve the fire retardant performance of the coating; for the BN@PDA-based EP composite coating, the back temperature is further reduced to 190.1°C, which reflects that the introduction of BN after PDA modification can effectively improve the carbon-forming ability of the polymer, thereby improving its thermal insulation effect; for the MOF and MOF@HCCP-based composite coating samples, the back temperature drops to the lowest (188.6°C and 179.2°C), which can be attributed to the HCCP and Co 2+ 、Zn 2+ ions; in contrast, the back surface temperature of the BN@PH composite material is 163.2 °C, which fully reflects the excellent flame retardant ability of the BN@PH composite material.

[0055] (7) The expansion characteristics of the composite coating are intrinsically linked to the thermal insulation effect of the formed carbon layer; the appearance of the expanded carbon layer obtained after high-temperature combustion of different samples is shown in Figure 2. Figure 7 The specific expansion parameters obtained are shown in Figure 8 As shown in the figure, the comparison shows that the expansion height and expansion rate of pure EP are significantly lower than those of other composite coating samples, which is consistent with its worst insulation effect. After adding BN and BN@PDA, the expansion height and expansion rate of the coating increased significantly to 15 mm, 17 mm and 11.7, 13.3, respectively. This is because the BN with self-carbonizing effect is retained in the carbon layer to prevent the escape of organic decomposition products and gas molecules. For the MOF composite coating, the expansion height and expansion rate further increased to 20 mm and 16.4, which is mainly due to the addition of Co 2+ 、Zn 2+ This result is caused by the catalytic effect: for the MOF@HCCP composite coating, the swelling height and swelling ratio increased to 27 mm and 21.1, which is due to the Co 2+ 、Zn 2+ The catalytic effect and the high phosphorus content of HCCP produce phosphoric acid molecules at high temperature to promote the formation of residual carbon; for the samples of BM@PH-based composite coatings, due to the high barrier properties and excellent thermal stability of BN, the role of metal ions in catalyzing the conversion of organic cracking products into carbon during combustion, and phosphorus-containing organic matter promoting the formation of residual carbon at high temperature, they show the largest expansion height and expansion rate (31mm, 24.2).

Claims

1. A method for preparing a hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fire retardant coating, comprising the following steps: (1) Preparation of BN@PDA-MOF@HCCP (BM@PH) flame retardant a. First, 0.5 g of boron nitride (BN) was ultrasonically dispersed in 100 mL of deionized water to obtain a uniformly dispersed boron nitride suspension; then, 0.2 g of tris-HCl was added to the boron nitride suspension and stirred evenly, and then 0.35 g of dopamine hydrochloride was added, and the pH of the boron nitride mixed solution was adjusted to 8.5 and continued to be stirred at room temperature for 24 h; finally, the mixture was repeatedly washed with deionized water to remove excess reactants, and the boron nitride / polydopamine (BN@PDA) hybrid was obtained by high-speed centrifugation; b. Ultrasonic dispersion of 0.5 BN@PDA in 100 mL methanol solution, and add 0.5 g Zn(NO3)2:6H2O and 0.5 g Co(NO3)2:6H2O powders thereto and stir for 10-20 min; then add 0.25 g HCCP to the BN@PDA dispersion and continue stirring for 5-10 min, and then add 0.95 g dimethylimidazole (2-MIM) to the BN@PDA dispersion; after stirring for 30 min, transfer the BN@PDA dispersion to a hydrothermal reactor and react at 140 °C for 16-20 hours; finally, the precipitate is washed by repeated centrifugation with methanol to obtain the BN@PDA-MOF@HCCP (BM@PH) flame retardant; (2) Preparation of BM@PH epoxy intumescent fire retardant coating Firstly, 10g melamine, 10g pentaerythritol and 20g ammonium polyphosphate were dispersed in deionized water and stirred vigorously until a uniform expansion system mixture was obtained; then, 4g BM@PH flame retardant was ultrasonically dispersed in deionized water to obtain a BM@PH flame retardant suspension, and the BM@PH flame retardant suspension, 38g water-based epoxy resin emulsion and 19g curing agent were mixed and stirred for 10-20 minutes and then poured into the expansion system mixture at one time to obtain a uniformly dispersed BM@PH-based water-based epoxy slurry; finally, the BM@PH-based water-based epoxy slurry was evenly coated on a steel plate with a sandblasting grade of Sa2, and after brushing, it was cured at room temperature for 7 days to obtain a BM@PH epoxy expansion fire retardant coating.

2. The method for preparing a hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fire retardant coating according to claim 1, characterized in that: In step 1(1), the mass ratio of dopamine hydrochloride to boron nitride is 1:1-2; the mass ratio of tris-HCl to dopamine hydrochloride is 1:1-1.5; the mass ratio of Zn(NO3)2:6H2O to BN@PDA is 1:1-2; the molar ratio of Zn(NO3)2:6H2O to Co(NO3)2:6H2O is 3-1:1; the molar ratio of Zn(NO3)2:6H2O to 2-methylimidazole is 1:4-8; the mass ratio of Zn(NO3)2:6H2O to HCCP is 1:0.4-1; the mass of BM@PH flame retardant in step 1(2) accounts for 3.0%-5.0% of the total mass of waterborne epoxy resin emulsion, curing agent, melamine, pentaerythritol, ammonium polyphosphate and BM@PH composite flame retardant.

3. A hexachlorocyclotriphosphazene bimetallic MOF microcapsule boron nitride-based fire retardant coating prepared by the method according to any one of claims 1 to 2.

Citation Information

Patent Citations

  • Preparation method and application of boron nitride-based composite anti-corrosion auxiliary agent

    CN112552727A

  • Preparation and application of ZnO@MOF@ polyphosphazene flame retardant

    CN112831174A

  • Preparation method of neodymium iron boron surface modified hexagonal boron nitride reinforced epoxy composite coating

    CN116285578A

  • Preparation method of BN / PAP-coated Cu-MOF-based epoxy flame-retardant material

    CN116376223A

  • Preparation method and application of multi-component core-shell structure flame retardant

    CN116396536A